Assessment of secondary students’ mathematical competencies - Leong, K.E.; Tan, J.Y. (2015)
This paper describes the assessment on the modeling competencies of two groups of Form 4 (16 year old) students in Malaysia. The analysis covered the mathematical competencies of identifying variables, making assumptions, mathematics reasoning and interpreting solutions. In addition, this study also reported the challenges and the difficulties students faced when solving the modeling task.